Nonaqueous electrolyte secondary battery

By using convex portions formed by large-particle inorganic particles in the filler layer in the spacer of the non-aqueous electrolyte secondary battery, the plastic deformation problem caused by charging and discharging is solved, and the capacity and safety of the battery are improved.

CN119234350APending Publication Date: 2024-12-31PANASONIC ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380041692.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-22
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing non-aqueous electrolyte secondary batteries have reduced battery capacity due to plastic deformation of the spacer during charging and discharging, and have an impact on battery characteristics and safety. The prior art has failed to effectively suppress such deformation.

Method used

A spacer with a base material layer and a filler layer is used, wherein the filler layer contains inorganic particles with an average particle size larger than the base material layer particles, and an inorganic portion with 10 to 35 convex portions exist in the 100μm x 100μm area is detected by scanning electron microscopy. Particles can relieve internal stress during charging and discharge and suppress plastic deformation of the spacer.

Benefits of technology

The plastic deformation of the spacer is effectively suppressed, and the charging and discharging cycle characteristics and safety of the nonaqueous electrolyte secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234350A_ABST
    Figure CN119234350A_ABST
Patent Text Reader

Abstract

Provided is a nonaqueous electrolyte secondary battery in which plastic deformation of a separator is suppressed. A non-aqueous electrolyte secondary battery according to one embodiment of the present invention is provided with an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, a non-aqueous electrolyte, and an outer can housing the electrode body and the non-aqueous electrolyte, the separator having a base layer and a filler layer formed on at least one surface of the base layer, the filler layer contains first inorganic particles and second inorganic particles having a larger average particle diameter than the first inorganic particles, and has protrusions formed from the second inorganic particles, and 10-35 second inorganic particles forming the protrusions are detected in a 100 [mu] m * 100 [mu] m region when the surface of the filler layer is observed with a scanning electron microscope.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-aqueous electrolyte secondary battery. Background Art

[0002] In recent years, non-aqueous electrolyte secondary batteries have been widely used as secondary batteries with high output power and high energy density. In non-aqueous electrolyte secondary batteries, lithium ions and the like are moved between the positive electrode and the negative electrode via a non-aqueous electrolyte to perform charging and discharging. The positive electrode and the negative electrode are oppositely disposed with a separator sandwiched therebetween, and the separator separates the positive electrode and the negative electrode from each other.

[0003] Patent Document 1 discloses a separator having a porous substrate layer and a heat-resistant filler layer. The separator has numerous concavities and convexities on the surface of the filler layer because the filler layer contains a filler having a large particle size. Patent Document 1 states that the electrolyte can be retained between the separator and the electrode by utilizing the numerous concavities and convexities formed on the surface of the filler layer.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-76289 Summary of the invention

[0007] However, secondary batteries have a situation where the battery capacity decreases due to repeated charge and discharge. The inventors of the present invention have conducted in-depth research and found that the increase or decrease in electrode thickness caused by charge and discharge causes the spacer to undergo plastic deformation and become thinner, thereby changing the distance between the electrodes and reducing the battery capacity. The plastic deformation of the spacer may also affect battery characteristics other than battery capacity. In addition, from the perspective of safety, it is also desirable to suppress the plastic deformation of the spacer. The technology disclosed in Patent Document 1 does not study the plastic deformation of the spacer, and there is still room for improvement.

[0008] An object of the present invention is to provide a non-aqueous electrolyte secondary battery in which plastic deformation of a separator is suppressed.

[0009] A nonaqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it comprises an electrode body formed by winding a positive electrode and a negative electrode with a separator sandwiched therebetween, a nonaqueous electrolyte, and an outer packaging can for accommodating the electrode body and the nonaqueous electrolyte, the separator having a substrate layer and a filler layer formed on at least one surface of the substrate layer, the filler layer comprising first inorganic particles and second inorganic particles having an average particle size larger than that of the first inorganic particles, and having protrusions formed by the second inorganic particles, and when the surface of the filler layer is observed using a scanning electron microscope, 10 to 35 second inorganic particles forming the protrusions are detected in an area of ​​100 μm×100 μm.

[0010] According to the nonaqueous electrolyte secondary battery of the present invention, plastic deformation of the separator can be suppressed, thereby improving battery characteristics such as charge and discharge cycle characteristics and safety of the nonaqueous electrolyte secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a longitudinal cross-sectional view of a cylindrical secondary battery as an example of an embodiment.

[0012] Figure 2 It is a cross-sectional view of a spacer as an example of an embodiment. DETAILED DESCRIPTION

[0013] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery of the present invention will be described in detail with reference to the accompanying drawings. Although a cylindrical secondary battery in which an electrode body is contained in a cylindrical outer packaging can is illustrated below, the outer packaging can is not limited to a cylindrical shape, and may be, for example, square, button-shaped, etc. It should be noted that in the following description, specific shapes, materials, numerical values, directions, etc. are examples for facilitating the understanding of the present invention, and may be appropriately changed to match the specifications of the non-aqueous electrolyte secondary battery. In addition, in the following description, in the case of including multiple embodiments and variations, it is initially envisioned that their characteristic parts are appropriately combined for use.

[0014] Figure 1 It is a longitudinal cross-sectional view of a cylindrical secondary battery 10 as an example of the embodiment. Figure 1 The cylindrical secondary battery 10 shown contains an electrode body 14 and a non-aqueous electrolyte (not shown) in an outer can 15. It should be noted that, for the convenience of description, the direction along the axial direction of the outer can 15 is set as "longitudinal or up and down direction", the sealing body 16 side is set as "up", and the bottom side of the outer can 15 is set as "down".

[0015] As a non-aqueous solvent (organic solvent) for a non-aqueous electrolyte, carbonates, lactones, ethers, ketones, esters, etc. can be used, and these solvents can be mixed and used in two or more kinds. In the case of mixing two or more solvents, a mixed solvent containing cyclic carbonates and chain carbonates is preferably used. For example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used as cyclic carbonates, and dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) can be used as chain carbonates. As esters, carbonates such as methyl acetate (MA) and methyl propionate (MP) are preferably used. The non-aqueous solvent may contain a halogen substitute in which at least a portion of the hydrogen atoms of these solvents are replaced by a halogen atom such as fluorine. As a halogen substitute, for example, fluoroethylene carbonate (FEC) and fluoromethyl propionate (FMP) are preferably used. As the electrolyte salt of the non-aqueous electrolyte, LiPF6, LiBF4, LiCF3SO3, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, etc. and mixtures thereof can be used. The amount of the electrolyte salt dissolved in the non-aqueous solvent is, for example, 0.5 mol / L to 2.0 mol / L.

[0016] The electrode body 14 has a wound structure in which a strip-shaped positive electrode 11 and a strip-shaped negative electrode 12 are wound with a separator 13 interposed therebetween. The positive electrode 11, the negative electrode 12, and the separator 13 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by winding into a spiral shape. In the electrode body 14, the positive electrode 11, the negative electrode 12, and the separator 13 are wound, for example, 10 to 30 times. In order to prevent the precipitation of lithium, the negative electrode 12 is formed with a size one circle larger than the positive electrode 11. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction (short side direction). The separator 13 is formed with a size one circle larger than the positive electrode 11 and the negative electrode 12, and two sheets are arranged in a manner of sandwiching the positive electrode 11. The positive electrode lead 19 is connected to the approximately center of the length direction of the positive electrode 11 by welding, and the negative electrode lead 20 is connected to the inner end of the winding of the negative electrode 12 by welding.

[0017] Insulating plates 17 and 18 are disposed above and below the electrode body 14 , respectively. Figure 1In the example shown, the positive lead 19 extends toward the sealing body 16 through the through hole of the insulating plate 17 and is connected to the lower surface of the filter 22 of the sealing body 16 by welding or the like. In the secondary battery 10, the cover 26, which is the top plate of the sealing body 16 and is electrically connected to the filter 22, becomes the positive terminal. On the other hand, the negative lead 20 extends toward the bottom side of the outer packaging can 15 through the through hole of the insulating plate 18 and is connected to the bottom inner surface of the outer packaging can 15 by welding or the like. In the secondary battery 10, the outer packaging can 15 becomes the negative terminal. It should be noted that when the negative lead 20 is arranged at the outer end of the winding, the negative lead 20 extends toward the bottom side of the outer packaging can 15 through the outer side of the insulating plate 18 and is welded to the bottom inner surface of the outer packaging can 15.

[0018] As described above, the outer can 15 is a metal container in a cylindrical shape with a bottom and an opening on one side in the axial direction. A gasket 27 is provided between the outer can 15 and the sealing body 16 to ensure the airtightness of the battery interior and the insulation between the outer can 15 and the sealing body 16. The outer can 15 is provided with a groove 21 formed by a part of the side portion bulging inward to support the sealing body 16. The groove 21 is preferably formed in an annular shape along the circumferential direction of the outer can 15, and the sealing body 16 is supported by its upper surface. The sealing body 16 is fixed to the upper part of the outer can 15 by using the groove 21 and the open end of the outer can 15 that is crimped to the sealing body 16.

[0019] The sealing body 16 has a structure in which a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25 and a cover 26 are stacked in order from the electrode body 14 side. The components constituting the sealing body 16 have, for example, a disc shape or a ring shape, and the components except the insulating member 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected at their respective central portions, and an insulating member 24 is sandwiched between their respective peripheral portions. When an abnormality occurs in the battery and the internal pressure rises, the lower valve body 23 is deformed and broken in a manner that pushes the upper valve body 25 toward the cover 26 side, thereby blocking the current path between the lower valve body 23 and the upper valve body 25. When the internal pressure rises further, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cover 26.

[0020] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , particularly the separator 13 , will be described in detail.

[0021] [positive electrode]

[0022] The positive electrode 11 includes a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode current collector can be made of a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface. The thickness of the positive electrode current collector is, for example, 10 μm to 30 μm.

[0023] The positive electrode mixture layer is preferably formed on both sides of the positive electrode collector. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm for one side of the positive electrode collector. The positive electrode mixture layer, for example, includes a positive electrode active material, a conductive agent, and a binder. For example, a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, a binder, etc. is applied to both sides of the positive electrode collector, and after the coating is dried, the coating is rolled using a roller or the like, thereby making a positive electrode.

[0024] Examples of the positive electrode active material contained in the positive electrode mixture layer include lithium transition metal composite oxides containing transition metal elements such as Co, Mn, and Ni. For example, lithium transition metal composite oxides are Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). These may be used alone or in combination of two or more.

[0025] In order to realize a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains a lithium nickel composite oxide. Examples of the lithium nickel composite oxide include Li x NiO2、Li x Co y Ni 1-y O2、Li x Ni 1-y M y O z (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3), etc. The higher the Ni content of the lithium nickel composite oxide, the higher the capacity.

[0026] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0027] Examples of the binder contained in the positive electrode mixture layer include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, and polyolefin-based resins, etc. These may be used alone or in combination of two or more.

[0028] [negative electrode]

[0029] The negative electrode 12 includes a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode current collector can be made of a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface. The thickness of the negative electrode current collector is, for example, 5 μm to 30 μm.

[0030] The negative electrode mixture layer is preferably formed on both sides of the negative electrode collector. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm for one side of the negative electrode collector. The negative electrode mixture layer, for example, contains a negative electrode active material and a binder. For example, a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. is applied to both sides of the negative electrode collector, and after the coating is dried, the coating is rolled using a roller or the like, thereby making a negative electrode.

[0031] The negative electrode active material contained in the negative electrode mixture layer is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and generally a carbon material such as graphite is used. The graphite can be any of natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite, and artificial graphites such as graphitized mesophase carbon microbeads.

[0032] As the negative electrode active material, metals such as Si and Sn that are alloyed with Li, metal compounds containing Si, Sn, etc., lithium-titanium composite oxides, etc. can also be used. x (0.5≤x≤1.6) Si-containing compounds or Li 2y SiO (2+y) A Si-containing compound represented by (0<y<2) in which Si fine particles are dispersed in a lithium silicate phase is used in combination with graphite.

[0033] Since the Si-containing compound has a large expansion and contraction rate due to battery charge and discharge, the separator 13 is easily plastically deformed when the negative electrode 12 contains the Si-containing compound. Therefore, when the negative electrode 12 contains the Si-containing compound, the effect of the separator 13 described later is significant.

[0034] Examples of the binder contained in the negative electrode mixture layer include styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (PAA-Na, PAA-K, etc., and partially neutralized salt), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more.

[0035] [Spacer]

[0036] The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other, and prevents the positive electrode 11 and the negative electrode 12 from contacting each other and causing a short circuit. Figure 2 It is a cross-sectional view of the spacer 13 as an example of embodiment. Figure 2 In the example shown, the positive electrode 11 is arranged on the upper side of the separator 13 , and the negative electrode 12 is arranged on the lower side.

[0037] like Figure 2 As shown, the separator 13 includes a substrate layer 13a and a filler layer 13b formed on at least one surface of the substrate layer 13a. In this embodiment, the filler layer 13b is opposite to the positive electrode 11, and the substrate layer 13a is opposite to the negative electrode 12. It should be noted that this example is not limited to the filler layer 13b and the negative electrode 12 may be opposite to the substrate layer 13a and the positive electrode 11. In addition, the separator 13 may also have filler layers 13b on both sides of the substrate layer 13a.

[0038] As the substrate layer 13a, for example, a porous sheet having ion permeability and insulation is used. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. The material of the substrate layer 13a is not particularly limited, and examples thereof include polyolefins such as polyethylene, polypropylene, copolymers of polyethylene and α-olefins, acrylic resins, polystyrene, polyesters, cellulose, polyimides, polyphenylene sulfide, polyetheretherketone, fluororesins, etc. The substrate layer 13a may be a single-layer structure or a multi-layer structure. The thickness of the substrate layer 13a is preferably 3 μm to 20 μm, and more preferably 5 μm to 15 μm.

[0039] The filler layer 13b includes first inorganic particles 30 and second inorganic particles 32 having an average particle diameter larger than that of the first inorganic particles 30, and has convex portions 32a formed by the second inorganic particles 32. In addition, when the surface of the filler layer 13b is observed using a scanning electron microscope (SEM, for example, SU8220 manufactured by Hitachi High-Tech Corporation), 10 to 35 second inorganic particles 32 forming the convex portions 32a are detected in an area of ​​100 μm×100 μm. As a result, the internal stress generated by the expansion and contraction of the positive electrode 11 and the negative electrode 12 during charge and discharge of the secondary battery 10 can be alleviated, and thus the plastic deformation of the separator 13 can be suppressed.

[0040] If the number of the second inorganic particles 32 forming the convex portions 32a detected is less than 10 per unit area (100 μm×100 μm), the filler layer 13b is in close contact with the electrode, and the effect of suppressing the plastic deformation of the spacer 13 is not fully manifested. In addition, if the number of the second inorganic particles 32 forming the convex portions 32a detected is more than 35, there is no sufficient space between the convex portions 32a, and the effect of suppressing the plastic deformation of the spacer 13 is not fully manifested.

[0041] The convex portion 32a may be, for example, of a size that can be detected by SEM observation performed by magnifying the surface of the filler layer 13b 1000 times. An area of ​​100 μm×100 μm on the surface of the filler layer 13b is observed, and the number of the second inorganic particles 32 forming the convex portion 32a detected by SEM observation is counted. Three different areas are observed, and the average value of the number detected in each area is set as the number of the second inorganic particles forming the convex portion per unit predetermined area (100 μm×100 μm).

[0042] like Figure 2 As shown, the second inorganic particles 32 forming the convex portion 32a are preferably in contact with the surface of the substrate layer 13a. The surface of the portion other than the convex portion 32a in the filler layer 13b is preferably substantially flat, and its thickness t is, for example, 1 μm to 5 μm. The average height of the convex portion 32a is preferably 1 μm or more and 9 μm or less relative to the surface of the portion adjacent to the convex portion 32a in the filler layer 13b. In the case where the surface of the portion other than the convex portion 32a in the filler layer 13b is flat, if the particle size of the second inorganic particles 32 in the thickness direction of the spacer 13 is set to d, the height of the convex portion 32a can be calculated by subtracting t from d. It should be noted that the average height of the convex portion 32a can be obtained by averaging the heights of all the convex portions 32a in a predetermined area (100 μm×100 μm). The average height of the convex portion 32a can be measured using a shape analysis laser microscope (e.g., VK-X1000 manufactured by Keyence). The cross-sectional shape of the second inorganic particles 32 may be circular or elliptical, and is not particularly limited.

[0043] As the material of the first inorganic particle 30, for example, metal oxides, metal nitrides, metal fluorides, metal carbides, etc. can be cited. As metal oxides, for example, aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, nickel oxide, silicon oxide, manganese oxide, etc. can be cited. As metal nitrides, for example, titanium nitride, boron nitride, aluminum nitride, magnesium nitride, silicon nitride, etc. can be cited. As metal fluorides, for example, aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, barium fluoride, etc. can be cited. As metal carbides, for example, silicon carbide, boron carbide, titanium carbide, tungsten carbide, etc. can be cited. In addition, the first inorganic particle 30 can also be zeolite (M 2 / n O·Al2O3·xSiO2·yH2O, M is a metal element, n is the valence of M, x≥2, y≥0) and other porous aluminosilicates, talc (Mg3Si4O 10 (OH)2) and other layered silicates, barium titanate (BaTiO3), strontium titanate (SrTiO3) and other minerals, etc. These may be used alone or in combination of two or more.

[0044] The material of the second inorganic particle 32 is preferably stable while having rigidity. The above-mentioned rigidity means that the shape can be maintained even when internal stress is generated inside the electrode body 14. The above-mentioned stability means that it is stable for non-aqueous electrolytes and does not participate in charge and discharge reactions, and is electrochemically stable. The material of the second inorganic particle 32 is at least one selected from oxides, sulfates, and hydroxides. As oxides, aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, etc. can be cited. As sulfides, barium sulfate, magnesium sulfate, aluminum sulfate, etc. can be cited. As hydroxides, aluminum hydroxide, magnesium hydroxide, aluminum hydroxide, etc. can be cited.

[0045] The average particle size (D50) of the first inorganic particle 30 is, for example, 0.3 μm to 0.8 μm. The D50 of the second inorganic particle 32 is, for example, 3 μm to 10 μm. In this specification, the average particle size (D50) means the particle size at which the cumulative frequency from the smaller particle size reaches 50% in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the inorganic particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac Bell) using water as a dispersion medium.

[0046] The filler layer 13b may further include a binder. The binder is a material that can form a film on the substrate layer 13a. The binder has the function of bonding the first inorganic particles 30 and the second inorganic particles 32 to the substrate layer 13a. The binder is preferably a polymer material, for example, fluorine resins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide resins, polyamide resins, acrylic resins, polyolefin resins, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. can be illustrated. They can be used alone or in combination of two or more.

[0047] In the filler layer 13 b , when the content of the first inorganic particles 30 is 100 parts by mass, the content of the second inorganic particles 32 is, for example, 1 to 10 parts by mass, and the content of the binder is, for example, 1 to 10 parts by mass.

[0048] Example

[0049] Hereinafter, the present invention will be further described using examples; however, the present invention is not limited to these examples.

[0050] <Example>

[0051] [Production of positive electrode]

[0052] As the positive electrode active material, LiNi 0.88 Co 0.09 Al 0.03 Lithium nickel cobalt oxide containing aluminum represented by O2. 100 parts by mass of a positive electrode active material, 1 part by mass of acetylene black (AB) and 0.9 parts by mass of polyvinylidene fluoride (PVDF) are mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added to prepare a positive electrode mixture slurry. Then, the positive electrode mixture slurry is applied to both sides of a strip-shaped positive electrode collector made of aluminum foil with a thickness of 15 μm, and after drying, it is rolled and cut into a specified electrode plate size to produce a positive electrode with a positive electrode mixture layer formed on both sides of the positive electrode collector. In the approximate center of the longitudinal direction of the positive electrode, a positive electrode exposure portion is provided where there is no mixture layer and the surface of the collector is exposed, and an aluminum positive electrode lead is welded to the positive electrode exposure portion.

[0053] [Production of negative electrode]

[0054] 95 parts by mass of graphite, 5 parts by mass of Si oxide (SiO), 1 part by mass of sodium carboxymethyl cellulose (CMC-Na) and 1 part by mass of styrene butadiene rubber (SBR) were mixed and an appropriate amount of water was added to prepare a negative electrode mixture slurry. Then, the negative electrode mixture slurry was applied to both sides of a strip-shaped negative electrode collector made of 8 μm thick copper foil, dried, rolled, and cut into a specified electrode plate size to produce a negative electrode with a negative electrode mixture layer formed on both sides of the negative electrode collector. At the inner end of the winding of the negative electrode, a negative electrode exposure portion where the mixture layer does not exist and the collector surface is exposed is provided, and a nickel negative electrode lead is welded to the negative electrode exposure portion.

[0055] [Making spacers]

[0056] As the substrate layer, a porous substrate made of polyethylene with a thickness of 12 μm was used. Alumina (α-Al2O3) particles with an average particle size (D50) of 0.7 μm as the first inorganic particle, magnesium hydroxide (Mg(OH)2) particles with a D50 of 5 μm as the second inorganic particle, and an acrylic binder emulsion were mixed at a solid content mass ratio of 100:4:3, and then an appropriate amount of water was added to make the solid content concentration 10% by mass to prepare a dispersion. The dispersion was applied to the entire surface area of ​​the porous substrate as the substrate layer using a micro gravure coater. Thereafter, the coating was dried by heating in an oven at 50°C for 4 hours to form a filler layer with Mg(OH)2 particles protruding from the surface of the binder with a thickness of 3 μm. As a result of observation using a scanning electron microscope (manufactured by Hitachi High-Tech Co., Ltd., SU8220), the number of second inorganic particles forming the projections per unit predetermined area (100 μm×100 μm) was 10. The average height of the projections was 2 μm.

[0057] [Preparation of non-aqueous electrolyte]

[0058] To 100 parts by mass of a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 3:7, 5 parts by mass of vinylene carbonate (VC) was added, and lithium hexafluorophosphate (LiPF6) was dissolved in the resulting solution at a concentration of 1.5 mol / L, thereby preparing a non-aqueous electrolyte.

[0059] [Manufacturing of secondary batteries]

[0060] The positive electrode and the negative electrode are wound into a spiral shape with a separator sandwiched therebetween to produce a wound electrode body. At this time, the filler layer of the separator is placed opposite to the positive electrode. Insulating plates are arranged above and below the above-mentioned electrode body, and the electrode body is housed in an outer packaging can. The negative electrode lead is welded to the bottom of the outer packaging can with a bottomed cylindrical shape, and the positive electrode lead is welded to the sealing body. After injecting a non-aqueous electrolyte into the outer packaging can, the opening of the outer packaging can is sealed with a sealing body with a gasket sandwiched therebetween, and then the non-aqueous electrolyte secondary battery is produced by standing in a constant temperature bath at 60°C for 15 hours. The capacity of the secondary battery produced is 4600mAh.

[0061] [Evaluation of the rate of change in spacer thickness]

[0062] After the secondary battery is charged at a constant current of 1380mA (0.3It) to a battery voltage of 4.2V, it is charged at a constant voltage of 4.2V to a current of 92mA (0.02It). Thereafter, it is discharged at a constant current of 4600mA (1.0It) to a battery voltage of 2.7V. The charge and discharge cycle is performed for 500 cycles while inserting a 20-minute rest time between each cycle. The secondary battery after 500 cycles is disassembled and the separator is taken out. The thickness of the separator is measured at a position that is 1 / 3 of the total length in the length direction from the inner end of the winding, and the measured value is set as the "thickness after cycle". Based on the "thickness after cycle" and the "initial thickness" of the separator measured in advance before loading the secondary battery, the rate of change of the separator thickness is calculated using the following calculation formula.

[0063] Change rate of spacer thickness (%) = (initial thickness - thickness after cycle) / (initial thickness) × 100

[0064] <Example 2>

[0065] A secondary battery was produced and evaluated in the same manner as in Example 1, except that the mixing ratio of Mg(OH)2 particles to 100 parts by mass of α-Al2O3 particles was changed to 7 parts by mass in the production of the separator. As a result of SEM observation, the number of the second inorganic particles forming the convex portion per unit area (100 μm×100 μm) was 16. The average height of the convex portion was 2 μm.

[0066] <Example 3>

[0067] A secondary battery was produced and evaluated in the same manner as in Example 1, except that the mixing ratio of Mg(OH)2 particles to 100 parts by mass of α-Al2O3 particles was changed to 14 parts by mass in the preparation of the separator. As a result of SEM observation, the number of the second inorganic particles forming the convex portion per unit area (100 μm×100 μm) was 35. The average height of the convex portion was 2 μm.

[0068] <Example 4>

[0069] A secondary battery was produced and evaluated in the same manner as in Example 1, except that Mg(OH)2 particles with a D50 of 4 μm were used instead of Mg(OH)2 particles with a D50 of 5 μm in the preparation of the separator, and the mixing ratio of Mg(OH)2 particles to 100 parts by mass of α-Al2O3 particles was changed to 14 parts by mass. As a result of SEM observation, the number of the second inorganic particles forming the convex portion per unit area (100 μm×100 μm) was 26. The average height of the convex portion was 2 μm. The average height of the convex portion was 1 μm.

[0070] <Example 5>

[0071] A secondary battery was produced and evaluated in the same manner as in Example 1, except that Mg(OH)2 particles with a D50 of 7 μm were used instead of Mg(OH)2 particles with a D50 of 5 μm in the preparation of the separator, and the mixing ratio of Mg(OH)2 particles to 100 parts by mass of α-Al2O3 particles was changed to 30 parts by mass. As a result of SEM observation, the number of the second inorganic particles forming the convex portion per unit predetermined area (100 μm×100 μm) was 28. The average height of the convex portion was 4 μm.

[0072] <Example 6>

[0073] A secondary battery was produced and evaluated in the same manner as in Example 1, except that Mg(OH)2 particles with a D50 of 10 μm were used instead of Mg(OH)2 particles with a D50 of 5 μm in the preparation of the separator, and the mixing ratio of Mg(OH)2 particles to 100 parts by mass of α-Al2O3 particles was changed to 32 parts by mass. As a result of SEM observation, the number of the second inorganic particles forming the convex portion per unit area (100 μm×100 μm) was 10. The average height of the convex portion was 7 μm.

[0074] <Comparative Example 1>

[0075] A secondary battery was produced and evaluated in the same manner as in Example 1 except that the Mg(OH) 2 particles were not mixed in the separator.

[0076] <Comparative Example 2>

[0077] A secondary battery was produced and evaluated in the same manner as in Example 1, except that the mixing ratio of Mg(OH)2 particles to 100 parts by mass of α-Al2O3 particles was changed to 2 parts by mass in the production of the separator. As a result of SEM observation, the number of the second inorganic particles forming the protrusions per unit area (100 μm×100 μm) was 6.

[0078] <Comparative Example 3>

[0079] A secondary battery was produced and evaluated in the same manner as in Example 1, except that the mixing ratio of Mg(OH)2 particles to 100 parts by mass of α-Al2O3 particles was changed to 18 parts by mass in the production of the separator. As a result of SEM observation, the number of the second inorganic particles forming the protrusions per unit predetermined area (100 μm×100 μm) was 45.

[0080] Evaluation results of the secondary batteries of Examples and Comparative Examples are shown in Table 1. Table 1 also shows the types and D50 of the first and second inorganic particles, and the number of the second inorganic particles forming the projections per unit area (100 μm×100 μm).

[0081]

[0082] The secondary battery of the embodiment has a lower rate of change in the thickness of the spacer than the secondary battery of Comparative Example 1. On the other hand, the rate of change in the thickness of the spacer of the secondary batteries of Comparative Examples 2 and 3 is about the same as that of the secondary battery of Comparative Example 1. It can be seen that by making the filler layer contain the second inorganic particles in such a manner that the number of the second inorganic particles forming the convex portion per unit predetermined area is 10 to 35, the plastic deformation of the spacer can be suppressed.

[0083] The present invention can be further described by the following embodiments.

[0084] Composition 1:

[0085] A non-aqueous electrolyte secondary battery comprises an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, a non-aqueous electrolyte, and an outer packaging can accommodating the electrode body and the non-aqueous electrolyte.

[0086] The spacer comprises a base material layer and a filler layer formed on at least one surface of the base material layer.

[0087] The filler layer includes first inorganic particles and second inorganic particles having an average particle size larger than that of the first inorganic particles, and has protrusions formed by the second inorganic particles.

[0088] Using a scanning electron microscope, 10 to 35 of the second inorganic particles forming the projections were detected in a 100 μm×100 μm region on the surface of the filler layer.

[0089] Composition 2:

[0090] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein an average height of the projections relative to a surface of a portion of the filler layer adjacent to the projections is 1 μm to 9 μm.

[0091] Composition 3:

[0092] The nonaqueous electrolyte secondary battery according to configuration 1 or 2, wherein the average particle size of the first inorganic particles is 0.3 μm to 0.8 μm, and the average particle size of the second inorganic particles is 3 μm to 10 μm.

[0093] Composition 4:

[0094] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the second inorganic particles forming the protrusions are in contact with the base layer.

[0095] Composition 5:

[0096] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the material of the second inorganic particles is at least one selected from oxides, sulfates, and hydroxides.

[0097] Description of Reference Numerals

[0098] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 13a substrate layer, 13b filler layer, 14 electrode body, 15 outer can, 16 sealing body, 17, 18 insulating plate, 19 positive electrode lead, 20 negative electrode lead, 21 slotted portion, 22 filter, 23 lower valve body, 24 insulating member, 25 upper valve body, 26 cover, 26a opening, 27 gasket, 30 first inorganic particle, 32 second inorganic particle.

Claims

1. A non-aqueous electrolyte secondary battery comprising an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, a non-aqueous electrolyte, and an outer packaging can for housing the electrode body and the non-aqueous electrolyte, The spacer comprises a base material layer and a filler layer formed on at least one surface of the base material layer. The filler layer includes first inorganic particles and second inorganic particles having an average particle size larger than that of the first inorganic particles, and has convex portions formed by the second inorganic particles. When the surface of the filler layer was observed with a scanning electron microscope, 10 to 35 of the second inorganic particles forming the protrusions were detected in a region of 100 μm×100 μm.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein An average height of the projections is 1 μm or more and 9 μm or less with respect to a surface of a portion of the filler layer adjacent to the projections.

3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The average particle size of the first inorganic particles is 0.3 μm to 0.8 μm, and the average particle size of the second inorganic particles is 3 μm to 10 μm.

4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The second inorganic particles forming the protrusions are in contact with the base layer.

5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The material of the second inorganic particles is at least one selected from oxides, sulfates, and hydroxides.

Citation Information

Cited By

  • Separator, secondary battery cell and electrical apparatus

    WO2026157485A1